Microfluidic Delivery of High Viscosity Liquids Using Piezoelectric Micropumps for Subcutaneous Drug Infusion Applications - Nivedha Surendran; Claudia Patricia Durasiewicz; Thalia Hoffmann; Axel Wille; Agnes Beate Bussmann; Martin Richter (IEEE Open Journal of Engineering in Medicine and Biology)
Goal: Auto-injectors for self-administration of drugs are usually refrigerated. If not warmed up prior to the injection, ejection of the total drug volume is not guaranteed, as their spring and plunger mechanism cannot adjust for a change in viscosity of the drug. Here, we develop piezoelectric micro diaphragm pump that allows these modifications possible while investigating the effectiveness of this alternative dosing method. Methods: The dosing of highly viscous liquid of 25 mPa·s is made possible using application-specific micropump design. By comparing the analytical with experimental results, the practicality of the concept is verified. Results: Using a powerful piezoelectric stack actuator, the micropump achieves high fluid pressures of up to (368 ± 17) kPa. In order to assess the influence of viscosity, we characterize the fluidic performance of the designed micropump through 27G gauge needle for various water-glycerin mixtures. We find maximum flow rates of 2 mL/min for viscosities of up to 25 mPa·s. Conclusions: The developed micro diaphragm pump enables the development of smart auto-injectors with flow rate regulation to achieve drug delivery for high viscosity drugs through 27G needles.